Penerapan Obstruction of Justice dalam Perkara Tindak Pidana Terkait Pasal 51 Ayat 2 Kitab Undang-Undang Hukum Pidana - Kholis, Akhmad Dinul; Sujono, Sujono; Sudarto, Sudarto (FOCUS, 2025)
Criminal threats for people who do not obey the orders of officials, as stipulated in Article 216 paragraph (1) of the Criminal Code which stipulates that anyone who intentionally does not obey orders or requests made according to the law by an official whose duty is to supervise something, or by an official based on his duties, as well as those who are given the authority to investigate or examine criminal acts; Likewise, anyone who intentionally prevents, obstructs or thwarts an action to carry out the provisions of the law carried out by one of the officials, is threatened with criminal penalties. So, Article 51 paragraph (2) is intended to protect the perpetrator of an order because there is an official order where the protection is something that can be considered reasonable. The research method used is normative juridical. The results of the research are Legal regulations against people who obstruct investigations in the perspective of the Criminal Code that the term obstruction of justice in the Criminal Code. However, several criteria that refer to this problem can be found in several articles in the Criminal Code, including; Article 221 paragraph (1), Article 231 and Article 233. The substance of obstruction of justice is regulated in Articles 21 to 24 of Law No. 31 of 1999 in conjunction with Law No. 20 of 2001 concerning Amendments to Law No. 31 of 1999 concerning the Eradication of Criminal Acts of Corruption. Obstruction of Justice in criminal cases related to Article 51 paragraph (2) of the Criminal Code that provides restrictions on the implementation of illegal office orders. This provision aims to ensure that unlawful superior orders cannot be used as justification to free subordinates from criminal responsibility.